Transformation processes in economy and their value: from the past in the digital future - E. V. Yakovleva (Омский научный вестник: Серия "Общество. История. Современность")
From a position of megatrend of the present essence and post-industrial content of the transformation processes in economy having objective character, having evolutionary and technological origin and, penetrating all fields of economy, including agriculture, the industry, research activity, education reveal, causing thereby profound social and economic changes and conceptual reconsideration of a role of material and intellectual resources in the conditions of formation and development of digitalization. The research objective assuming realization of the corresponding tasks is the analysis and identification of regularities of the current trends of economic development allowing to create strategic vision of prospects of dynamics of social and economic systems of various level in this context. Results of a research are presented in article in the form of the state-of-the-art review